The search for democratic renewal : the politics of consultation in Britain and Australia - Manwaring, Rob (Manchester University Press, 2014)
Why is the search for democratic renewal so elusive? This book examines both the political and policy implications of efforts by the centre-left to transform democracy. This is a story not only about democratic change, but also the identity crisis of centre-left political parties.
Keywords: Labour Party (Great Britain) -- History.; Australian Labor Party -- History.; Australian Labor Party; Labour Party (Great Britain); Democracy -- Great Britain.; Democracy -- Australia.; Political participation -- Great Britain.; Political participation -- Australia.; Great Britain -- Politics and government.; Australia -- Politics and government.; Participation politique -- Grande-Bretagne.; Participation politique -- Australie.; Grande-Bretagne -- Politique et gouvernement.; Australie -- Politique et gouvernement.; Socialism and left-of-centre democratic ideologies.; POLITICAL SCIENCE -- Political Ideologies -- Communism, Post-Communism & Socialism.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Democracy; Political participation; Politics and government; Australia; Great Britain; Demokrati.; Politiskt deltagande.; Politiska förhållanden.; Historia.; Society & Social Sciences -- Politics & government -- Political ideologies.; History